Efficacy and Safety of Granulocyte-Colony Stimulating Factor Therapy in Chagas Cardiomyopathy: A Phase II Double-Blind, Randomized, Placebo-Controlled Clinical Trial - Macedo, Carolina T.; Larocca, Ticiana F.; Noya-Rabelo, Márcia; Aras, Roque; Macedo, Cristiano R. B.; Moreira, Moisés I.; Caldas, Alessandra C.; Torreão, Jorge A.; Monsão, Victor M. A.; Souza, Clarissa L. M.; Vasconcelos, Juliana F.; Bezerra, Milena R.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim Previous studies showed that granulocyte-colony stimulating factor (G-CSF) improved heart function in a mice model of Chronic Chagas Cardiomyopathy (CCC). Herein, we report the interim results of the safety and efficacy of G-CSF therapy vs. placebo in adults with Chagas cardiomyopathy. Methods Patients with CCC, New York Heart Association (NYHA) functional class II to IV and left ventricular ejection fraction (LVEF) 50% or below were included. A randomization list using blocks of 2 and 4 and an allocation rate of 1:1 was generated by R software which was stratified by functional class. Double blinding was done to both arms and assessors were masked to allocations. All patients received standard heart failure treatment for 2 months before 1:1 randomization to either the G-CSF (10 mcg/kg/day subcutaneously) or placebo group (1 mL of 0.9% saline subcutaneously). The primary endpoint was either maintenance or improvement of NYHA class from baseline to 6–12 months after treatment, and intention-to-treat analysis was used. Results We screened 535 patients with CCC in Salvador, Brazil, of whom 37 were randomized. Overall, baseline characteristics were well-balanced between groups. Most patients had NYHA class II heart failure (86.4%); low mean LVEF was 32 ± 7% in the G-CSF group and 33 ± 10% in the placebo group. Frequency of primary endpoint was 78% (95% CI 0.60–0.97) vs. 66% (95% CI 0.40–0.86), p = 0.47, at 6 months and 68% (95% CI 0.43–0.87) vs. 72% (95% CI 0.46–0.90), p = 0.80, at 12 months in placebo and G-CSF groups, respectively. G-CSF treatment was safe, without any related serious adverse events. There was no difference in mortality between both arms, with five deaths (18.5%) in treatment vs. four (12.5%) in the placebo arm. Exploratory analysis demonstrated that the maximum rate of oxygen consumption during exercise (VO2 max) showed an improving trend in the G-CSF group. Conclusion G-CSF therapy was safe and well-tolerated in 12 months of follow-up. Although prevention of symptom progression could not be demonstrated in the present study, our results support further investigation of G-CSF therapy in Chagas cardiomyopathy patients. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT02154269].